Nacido y criado - Trapero, Pablo 1971-; Rulloni, Mario; Pfening, Guillermo 1978-; Esquerro, Federico 1977-; Gusman, Martina 1978-; Nieto, Guillermo 19XX- (SBP, 2015)
"In Patagonia, a successful interior designer's life falls apart after he suffers a horrific accident"--IMDB, viewed May 20, 2015
Special features include: Work in progress; Shooting; Casting; Burns; Filming south; Post; Deleted scenes; Trailer; TV spot
Originally released as a motion picture in 2006
Keywords: Interior decorators / Drama; Families / Drama; Families; Interior decorators; Motion pictures / Argentina; Drama; Feature films; Motion pictures; Video recordings for the hearing impaired; Film; DVD-Video